Public Policies and Mental Health in Chile Today - Gonzalo Miranda Hiriart (Social Medicine Publication Group, 2024)
As part of the Chilean Student movement, graduate students in the Masters Program in Clinical Psychology at the University of Chile organized a protest forum on July 13th, 2011. The protest took place on the steps of the University's central building and was entitled "History, Public Policy, and Mental Health." During the protest various academics made presentations and led discussions with the audience (which included pedestrians walking along Alameda Ave in the center of the city). This article is a transcription of one of those presentations. It questions the public health policies which were implemented in Chile during the last several decades and looks at their consequences.